Historical Reference and Theatrical Autoreference - Čale Feldman, Lada (Array, 2000)
The article is a comparison between the contemporary historiograpohic metafiction and historiographic metadrama in their intentions, devices, and discussion of the relationship between histoire evenementielle and its textualizations, pointing to the specificity, complexity and diversity of metadrama. It offers a complex interplay of referential modalities, combining pseudoihistorical, historical, and auto-references, anachronisms, etc. (examples: from German and Croatian 20th cent. drama).